Natural Convective Heat Transfer from Horizontal and Near Horizontal Surfaces - Oosthuizen, Patrick H. (SpringerBriefs in Thermal Engineering and Applied Science,, 2018)
This book deals with a natural convective heat transfer situation of significant practical importance that has not been adequately dealt with in existing texts or widely available review papers: natural convective heat transfer from horizontal and near horizontal surfaces. The aim is to provide the reader with an understanding of past studies of natural convective heat transfer from horizontal surfaces and a more detailed review of contemporary studies. The more recent work deals with heat transfer from surfaces that have more complex shapes than previously considered, with heat transfer in situations in which laminar, transitional, and turbulent flow occur; in situations where the surface is inclined at a relatively small angle to the horizontal; and in situations where there is a covering surface above the heated surface. The authors further present methods for predicting heat transfer rates in all of the situations.